THE IMPACT OF KNOWLEDGE, WORK EXPERIENCE, AND MOTIVATION ON THE PERFORMANCE OF STATE CIVIL SERVANTS - Patintingan, Porferius Wandi; Sari Dewi, Andi Ratna; Musa, Andi Ernie Zaenab (Journal of Entrepreneur, Business and Management, 2024)
The purpose of this study was to determine the partial and simultaneous influence of the variables studied, where this study used a quantitative approach with a sample of 35 respondents with multiple regression analysis methods assisted by the SPSS application version 21. In this study, it was found that partially or simultaneously education, work experience and motivation had a significant effect on employee performance.